Digitalisasi Pengelolaan Perpustakaan Organisasi Pelajar Pondok Modern Gontor Ponorogo - Mohammad Mahasim Soleh; Yusuf Al Manaanu; Alif Cahya Setiyadi; Fadhil Muhammad; Muhammad Dliya Elhaq; Fajar Amin; Madani Ahmadan; Abdurrahman Muhammad (Ruang Pengabdian: Jurnal Pengabdian kepada Masyarakat, 2025)
Library management plays an essential role in supporting access to and dissemination of knowledge within educational institutions. This paper discusses a community service program aimed at developing a digital system for library management at the Student Organization of Pondok Modern (OPPM), Pondok Modern Darussalam Gontor, Mlarak, Ponorogo. The program was carried out through collaboration between the community service team and library administrators, encompassing software selection, staff training, and improvements to information technology infrastructure. Participants included 10–20 library staff members who took part in the training and 30–100 students who served as survey respondents. Data were collected through observation, interviews, surveys, and documentation, and then analyzed using descriptive quantitative and qualitative techniques. The evaluation results indicate significant improvements, with access to library collections increasing by approximately 30–50% and the efficiency of borrowing and returning books improving by 40–60%. This study not only provides a comprehensive overview of the effectiveness of library digitalization but also offers practical references for other educational institutions, while emphasizing the importance of stakeholder collaboration in the successful transformation of library management in the digital era.